Regularities of the influence of submicron ceramic powders TiO2, AlN, Cr2O3 on the tribological properties of a friction material - Leshok, A.V.; Dykha, A.V. (Problems of Tribology, 2021)
Friction units for automotive and special vehicles are designed to operate under boundary friction conditions. Modern vehicles contain friction assemblies that use friction materials. Currently, friction materials are actively used: based on thermosetting resins; pulp and paper-based materials; sintered powder materials; materials of carbon or carbon composition; materials with a ceramic matrix. The development of a unified understanding of the effect of the size and chemical nature of ceramic additives on the processes occurring in a friction material during friction is very important and can be obtained both on the basis of experimental and theoretical studies. The paper presents the results of a study of the effect of submicron TiO2, Cr2O3, AlN powders with a size of 0.2-0.5 microns on the tribotechnical properties of a frictional material based on copper intended for operation under boundary friction conditions. It was found that when using the addition of Cr2O3 powder, the greatest increase in the value of the friction coefficient is noted - from 0.042 to 0.082, a slightly smaller increase in the friction coefficient is shown by the use of AlN and TiO2 defects - 0.042-0.074 and 0.042-0.060, respectively. The least wear of the friction material was obtained when using 3.0 vol. % aluminum nitride additive - 2.1 microns / km. Increasing the addition of any of the submicron powders by more than 7 vol. % leads to a significant decrease in wear resistance. This is due to the formation on the surface of the friction material of a modified layer containing ceramic particles and the metallic phase of the friction material. For the friction material, an unstable value of the friction coefficient and increased wear were recorded